A Comprehensive Model for Resistance Economy Based on the Operations and Information Management in Iran - Mousapour Gorji, Mohammad Ali; Zareimatin, Hasan; Yazdani, Hamid Reza (ExcelingTech, 2019)
Abstract-There is no particular model for economic management in Iran. In the current circumstances where Iranian economy is under international embargos, resistance economy can guarantee national independence by acting as a model for domestic economy. Development of intellectual capital is the main criterion of national development and can also introduce synergy in resistance economy. The present paper aims to propose a comprehensive model for resistance economy based on the role of intellectual capital in Iran and the operations and information management via a mixed research method. The purpose of this study was to investigate the effects of information values in the value chain on gaining competitive advantage by considering the effect of the strategic alignment of the IT program and the organization's strategies. First, the Supreme Leaders views on resistance economy, library references, and semi-structured interviews with 15 faculty membersselected using purposive samplingwere analyzed using the grounded theory. The concepts derived from case studies were categorized as 475 and 61 primary and final concepts, respectively, and then modeled and classified as 30 influential parameters in four aspects of capital (human, psychological, social, and spiritual capital). In addition, the tests were verified and the model was validated via quantitative data analysis.